1998
DOI: 10.1159/000008583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Solutions of Bretschneider, St. Thomas’ Hospital and the National Institutes of Health for Cardioplegic Protection during Moderate Hypothermic Arrest

Abstract: We evaluated three cardioplegic solutions, Bretschneider’s cardioplegic solution (HTK), St. Thomas’ Hospital solution (STH) and the solution of the National Institutes of Health (NIH), a solution with added nitroglycerin and lidocaine, for their ability to minimize ischemia-reperfusion injury in a working rat heart model. After cardioplegic arrest at 4°C and subsequent 45 min of ischemic storage at 25°C the function recovery of hearts was examined during 1 h of normothermic crystalloid reperfusion using Krebs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…As aforementioned, UW has a higher viscosity, may cause vasoconstriction due to its relatively high potassium concentrations [18] , and has a potential erythrocyte-aggregating effect [4] . In contrast, perfusion with HTK may allow for higher flows and also for more efficient cooling than UW, and has demonstrated superior properties to preserve ATP concentrations in the mild hypothermic range of 15-32 ° C, which is typically found in the initially cooling process during organ flushing [19,20] . In a protocol that applies kidney machine perfusion prior to transplantation, Daemen et al [21] have already demonstrated a possible benefit of combining HTK and UW for kidney preservation in non-heart-beating donors after warm ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, UW has a higher viscosity, may cause vasoconstriction due to its relatively high potassium concentrations [18] , and has a potential erythrocyte-aggregating effect [4] . In contrast, perfusion with HTK may allow for higher flows and also for more efficient cooling than UW, and has demonstrated superior properties to preserve ATP concentrations in the mild hypothermic range of 15-32 ° C, which is typically found in the initially cooling process during organ flushing [19,20] . In a protocol that applies kidney machine perfusion prior to transplantation, Daemen et al [21] have already demonstrated a possible benefit of combining HTK and UW for kidney preservation in non-heart-beating donors after warm ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Like other cold crystalloid cardioplegia solutions, it arrests and cools the heart, decreasing its metabolic requirements during ischemia. In addition to this, it contains histidine (H) which provides a strong buffer capacity, tryptophan (T) which has cell mem- brane-protective effects, and ␣ -ketoglutarate (K) which is thought to aid ATP production [22] . There has been considerable progress in understanding the role of the MPTP in IR injury and the effect of blocking the MPTP with CsA is well documented [5-14, 16, 17, 23-25] .…”
Section: Discussionmentioning
confidence: 99%
“…After thoracotomy, the hearts were excised under topical cooling, immersed in cold Krebs-Henseleit buffer (KHB; 4°C) solution, and mounted on the aortic cannula. Then, according to the Langendorff technique, a nonrecirculating retrograde perfusion was initiated [13] (Fig. 1).…”
Section: Animalsmentioning
confidence: 99%
“…Measurement of hemodynamic parameters and collection of perfusate for the determination of enzyme and lactate releases were performed after 15 min of preischemic Langendorff perfusion and after the storage period as previously described in detail [13] ( Fig. 1).…”
Section: Measurement Of Cardiac Functionmentioning
confidence: 99%
See 1 more Smart Citation